Computer-aided Aviation English Testing on Example of RELTA Test - Zokić, Mira; Lazić, Nikolaj; Boras, Damir (2012)
Air safety depends on good communication. Aviation English testing is considered to be of vital importance for pilots and air traffic controllers. Several tests have been developed and used to test English language proficiency in aviation context and they all have similar way of testing. Testing, as well as preparation for testing, is partly computer-aided and partly face-to-face interaction between trainer/tester and candidate/test taker. This paper gives an overview of English language training and testing in aviation context, providing an insight into the current situation in Croatia and challenges that teachers, trainers, examiners and evaluators have been facing in Aviation English training and testing.
ENG